Expression analysis of surface molecules on human thymic dendritic cells with the 10th HLDA Workshop antibody panel - Gurka, Stephanie (Clin Transl Immunology, 2015)
Dendritic cells (DC) in the thymus have an important role in the establishment of central tolerance by promoting negative selection of autoreactive T cells and regulatory T-cell differentiation. Whereas human DC have recently been studied in various tissues in more detail, thymic DC subsets are still ill-defined. In the present work, we studied the binding of 71 monoclonal antibodies (mAb) submitted to the HLDA10 workshop to human CD123(+) plasmacytoid DC and the two subsets of conventional DC (cDC, CD141(+) and CD11b(+)) isolated from thymus tissue of infants undergoing corrective heart surgery. Within the panel, we found mAb binding to thymic pDC and both cDC subsets (for example, anti-Clec12A, TIM-3, Clec4A, CCR5, Axl, FLT3), but most of them additionally reacted with other thymic cell types. MAb directed to CD85h (ILT1) and the C-type lectin Clec7A (now CD369) reacted selectively with both cDC subsets, but not with other cells. Only one mAb directed to CD85g (ILT7) stained thymic pDC in a highly specific manner. Clec9A (DNGR1, now CD370) was the only tested HLDA10 antigen exclusively expressed on thymic CD141(+) cDC. The present report summarizes all data obtained.